(untitled) - Galvin, Kathleen M. (Lincolnwood, Illinois, 1994)
A textbook describing the communication process and skills needed for effective interpersonal communication and public speaking.
Keywords: Public speaking,Communication,Nói trứơc công chúng,Thông tin; Juvenile literature